Some Existence Results for a System of Nonlinear Fractional Differential Equations - Eskandar Ameer; Hassen Aydi; Hüseyin Işık; Muhammad Nazam; Vahid Parvaneh; Muhammad Arshad (Journal of Mathematics)
In this paper, we show that a sequence satisfying a Suzuki-type JS-rational contraction or a generalized Suzuki-type Ćirić JS-contraction, under some conditions, is a Cauchy sequence. This paper presents some common fixed point theorems and an application to resolve a system of nonlinear fractional differential equations. Some examples and consequences are also given.